Agronomic performance of lettuce subjected to green manure with different leguminous species - José J. A. Sarmento; José J. F. dos Santos; Caciana C. Costa; Marinês P. Bomfim (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Green manure is the practice of cultivation and incorporation of plants to the soil, mainly leguminous species, produced or not in situ, for the purpose of preserving and/or restoring soil organic matter and soil nutrients. To compare the effects of incorporating leguminous species in the pre-planting green manure on lettuce production, seven treatments were tested: mineral fertilization; crotalaria (Crotalaria juncea); cowpea (Vigna unguiculata); common bean (Phaseolus vulgaris); lablab bean (Dolichos lablab); pigeon pea (Cajanus cajan) and spontaneous plants. The treatments were arranged in the randomized blocks, with five repetitions. The experiment was conducted in the experimental area of the CCTA/UFCG, in the period from April to December 2016. At 30 days after transplanting, the following variables were analyzed: number of leaves, head diameter, shoot height, root volume, fresh weight of shoots and roots, dry weight of shoots and roots, total fresh weight of shoots and roots, total dry weight of shoots and roots and yield. The results were subjected to analysis of variance and, when significant, Tukey test at 0.05 probability level was applied to compare the means. The results showed that, among the leguminous species, the use of lablab bean led to greater development and yield of lettuce.